People Attitude Toward Promotion of Agroforestry Practices in Buffer Zone Area of Mt. Elgon National Park, Uganda - Buyinza Mukadasi; Nabalegwa Wambede (Fakultas Kehutanan Universitas Gadjah Mada, 2007)
Agroforestry is a historical practice in Uganda where people raised trees, crops and animals together traditionally on the same unit of farmland. This study was conducted to assess the attitude of people regarding the contribution of agroforestry practices in socio-economic development in the buffer zone area of Mutushet and Kortek, Mt. Elgon National Park, Uganda.Primary data were collected through formal household interviews with the use of a structured questionnaire administered to five percent households selected randomly in the Village Environmental Committees (VECs). In addition, key informant interviews and informal group discussions were also held. Altogether 146 households were interviewed. Data were analyzed using Chi-square test.Results show that the attitude of people towards contribution of agroforestry practices is independent of VECs, ethnic group, settlement period, and family size and depends on occupation, literacy level, distance from National Park boundary, damage caused by wild animals, land holding size and number of livestock holding. The important policy recommendation drawn from these findings is that intensive extension and motivation programs should be launched in those areas where the majority of people have unfavourable attitude towards agroforestry practices.